Revitalization of Value and Meaning Toba Batak Folkrole in The Formation of Character Education of Children - Leylia Khairani (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Folklore originated from the oral tradition of society, full of message of value and morals to be convened in one generation to the next generation.